EFFECT OF FOLIAR ACID APPLICATION ON THE TOTAL AND AVAILABLE IRON CONTENTS, AND CHLOROPHYLL CONTENT IN TOMATO PLANT(Lycopersicum Esculentum L.) GROWN WITH NUTRIENT SOLUTION - İbrahim ERDAL; Melek GÜRBÜZ; Ceyhan TARAKÇIOĞLU (Pamukkale University Journal of Engineering Sciences, 1998)
In this study, the effects of foliar application of dilueted acid ( 0.1 % of H2SO4 ) on dry matter, total and available Fe, total N and chlorophyll content of tomato plants grown with different nitrogen sources were investigated and the possibility of recovery in Fe-deficient plants by spraying the foliars with H2SO4 without the necessisity of Fe- fertilization was aimed. Diluted acid applied to foliars twice with a week interval. The highest dry matter was obtained in the plants grown with ammonium application, while the highest total N content was determined in urea-fed plants. Foliar acid application caused to increase both dry matter and total N content significantly. Total and available Fe increased by foliar acid application in the plants grown with urea and nitrate, however these increments were not statistically significant. Total Fe was negatively affected by foliar acid application in the plants grown with ammonium. Foliar acid application didn't affect chlorophyll content of the plants grown with urea, however significantly increased those of the plants grown with nitrate and ammonium.